Perancangan Website Jasa Titip Sebagai Fasilitator Transaksi Global - Aryanti Nur Anisah; Aminatus Sholikah Putri; Fatimah Nur Alifiah; Mochammad Zulfikar; Rhexy Pasha Dwi Olivia; Achmad Zidan Ramdani; Asmaul Khusna; Ronggo Alit (Pusat Riset dan Inovasi Nasional, 2024)
The advancement of technology has transformed the way trade is conducted, with the internet becoming the primary platform for business. E-commerce, or online trading, has opened significant opportunities for both sellers and buyers. Furthermore, online personal shopping services have gained popularity, enabling buyers to obtain goods from abroad or remote areas. However, the use of social media and informal communication limits the ease of finding and trusting personal shoppers. In order to address these challenges, this research introduces the